Effects of Carrier Heating on Raman Susceptibility of Weakly-Polar Semiconductor Magneto-Plasmas - Gopal, Gopal; Sharma, B. S.; Singh, Manjeet (Trends in Sciences, 2022)
In this paper, we develop a mathematical model to study the effects of carrier heating induced by a laser beam on Raman susceptibility of weakly-polar semiconductor magneto-plasmas. Using coupled mode approach, we obtain expressions for the real and imaginary parts of Raman susceptibility (Re⁡( χ_R),Im⁡( χ_R)) under hydrodynamic and rotating-wave approximations. In order to validate the results, we perform numerical analysis for n-InSb crystal - CO2 laser system. We observed change of sign of Re⁡( χ_R) as well as Im⁡( χ_R) around resonances. The carrier heating induced by the intense laser beam modifies the momentum transfer collision frequency of plasma carriers and consequently the Raman susceptibility of the semiconductor magneto-plasma, which subsequently enhances Re⁡( χ_R) and Im⁡( χ_R), (ii) shifts the enhanced Re⁡( χ_R) and Im⁡( χ_R) towards smaller values of applied magnetic field, and (iii) broadens the applied magnetic field regime at which change of sign of Re⁡( χ_R) and Im⁡( χ_R) are observed. The analysis leads to better understanding of Raman nonlinearity of semiconductor plasma and suggests an idea of development of Raman nonlinearity based optoelectronic devices. HIGHLIGHTS Effects of carrier heating on the real and imaginary parts of Raman susceptibility of weakly-polar semiconductor magneto-plasmas are investigated We observed alteration of sign of real and imaginary parts of Raman susceptibility around resonances Carrier heating induced by the intense laser beam: Enhances real and imaginary parts of Raman susceptibility, Shifts the enhanced real and imaginary parts of Raman susceptibility towards smaller values of applied magnetic field, and Broadens the applied magnetic field regime at which sign alteration of real and imaginary parts of Raman susceptibility are observed. GRAPHICAL ABSTRACT